Biaxially strained MoS₂ nanoshells with controllable layers boost alkaline hydrogen evolution - Zhang, Tao (2022)
Strain in layered transition-metal dichalcogenides (TMDs) is a type of effective approach to enhance the catalytic performance by activating their inert basal plane. However, compared with traditional uniaxial strain, the influence of biaxial strain and the TMD layer number on the local electronic configuration remains unexplored. Herein, via a new in situ self-vulcanization strategy, biaxially strained MoS2 nanoshells in the form of a single-crystalline Ni3 S2 @MoS2 core-shell heterostructure are realized, where the MoS2 layer is precisely controlled between the 1 and 5 layers. In particular, an electrode with the bilayer MoS2 nanoshells shows a remarkable hydrogen evolution reaction activity with a small overpotential of 78.1 mV at 10 mA cm-2 , and negligible activity degradation after durability testing. Density functional theory calculations reveal the contribution of the optimized biaxial strain together with the induced sulfur vacancies and identify the origin of superior catalytic sites in these biaxially strained MoS2 nanoshells. This work highlights the importance of the atomic-scale layer number and multiaxial strain in unlocking the potential of 2D TMD electrocatalysts.